2021
DOI: 10.1063/5.0073924
|View full text |Cite
|
Sign up to set email alerts
|

High concentration propane depletion with photocatalysis

Abstract: Our work is aimed at studying the abatement of volatile organic compounds produced by photocatalysts working in different light spectra, investigating the best catalyst able to treat propane in air mixtures at high concentrations of the order of thousands of ppm. The experimental data were analyzed in order to extract the relevant parameters and to compare the catalytic activities of three different photocatalysts, TiO2, WO3, and their mixtures. In a reactor box of 1.5 l, photocatalysis processing with TiO2 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Transition metal oxide catalysts in combi-nation with plasma have attracted growing interest for pollution abatement because of their comparable performance and low cost. In our previous work, we found that the TiO 2 and/or WO 3 catalysts alone are not able to efficiently remove propane [31], while here, we managed to increase the pentane depletion by using plasma together with a catalyst, thus yielding an efficient abatement of the intermediate reaction products.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Transition metal oxide catalysts in combi-nation with plasma have attracted growing interest for pollution abatement because of their comparable performance and low cost. In our previous work, we found that the TiO 2 and/or WO 3 catalysts alone are not able to efficiently remove propane [31], while here, we managed to increase the pentane depletion by using plasma together with a catalyst, thus yielding an efficient abatement of the intermediate reaction products.…”
Section: Discussionmentioning
confidence: 78%
“…In fact, our previous study [31] demonstrated a much lower abatement efficiency for propane, performed by catalysis processing and using only UV-A light energy. In the case of TiO 2 , we used light with a UV-A range of 340-400 nm and a peak at 370 nm to obtain an efficiency of less than 10% of the abatement after 22 min of application [31,32].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation